2008
DOI: 10.1016/j.biortech.2007.04.067
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel sponge-submerged membrane bioreactor (SSMBR) for sustainable water reclamation

Abstract: A novel sponge-submerged membrane bioreactor (SSMBR) to treat a high strength wastewater for water reclamation was developed in this study. The performance of this system was evaluated using two kinds of polyester-urethane sponges (coarse sponge with higher density S28-30/45R and fine sponge with lower density S16-18/80R) with sponge volume fraction of 10% and bioreactor MLSS of 10 g/L. The results indicated the addition of sponge in SMBR could increase sustainable flux (2 times for S28-30/45R and 1.4 times fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…For example, the application of polyester-urethane sponges (coarse sponge with higher density S 28-30 /45R and fine sponge with lower density S 16-18 /80R) with sponge volume fraction of 10%, indicated that the addition of sponge could increase COD removal efficiency (Ngo et al 2008). …”
mentioning
confidence: 99%
“…For example, the application of polyester-urethane sponges (coarse sponge with higher density S 28-30 /45R and fine sponge with lower density S 16-18 /80R) with sponge volume fraction of 10%, indicated that the addition of sponge could increase COD removal efficiency (Ngo et al 2008). …”
mentioning
confidence: 99%
“…The complex interaction of hydrodynamics, mass transfer, biological degradation, and existing compounds makes it difficult to isolate all the parameters that could help in predicting membrane fouling , although the most Defrance and Jaffrin 1999;Vyas et al 2002), the filtration time (short-term vs. long-term; Yang et al 2006;Zhang et al 2006), the operating conditions and cleaning procedures (Sanguanpak et al 2015a;Trussell et al 2006;Cui et al 2003), the setup configuration (external vs. submerged; Xue et al 2015) and the initial stage of the membrane (new vs. cleaned; Le Clech et al 2003). Irrespective, MBR users have resorted to several methods to control fouling such as back-pulsing or bubbling (Prieske et al 2010), the use of additives or sponge-like carriers (Ngo et al 2008), pre-settling of biomass (Ivanovic and Leiknes 2008), sludge granulation, and membrane surface change .…”
Section: Mbr Limitationsmentioning
confidence: 98%
“…These exploit a variety of (bio-)chemical, mechanical, or hydrodynamic means, such as the development of anti-fouling membranes [9,12], the use of additives (e.g., [61][62][63]), sponge-like carriers (e.g., [64]) or other circulating abrasive particles [65], sludge granulation (e.g., [66]), presettling of biomass from the bulk [65,67], membrane surface modification (e.g., [12,68]), etc.…”
Section: Membrane Foulingmentioning
confidence: 99%